So I assume you mean the square root and square root of 27=square root of (9x3)=3(square root (3))
The square root of 27 is 9 root 3.
81
If you actually mean "square root of 27", then the answer is 3√3
sqrt(27) = 3*sqrt(3).
So I assume you mean the square root and square root of 27=square root of (9x3)=3(square root (3))
The square root of 27 is 5.196152423...The square root of 27 is 5.19615242.5.19615242 x 5.19615242 = 27Simplified, the square root of 27 is 3 times the square root of 3.6.256 6.256
-27 does not have a square root. The mathematical expression for the square root of-1 is i.
root 27 = root 9 x root 3 = 3 root 3. Dividing this by root 3 gives 3!
√3 x √27 = 9
The square root of 27 is 9 root 3.
To simplify the square root of 27 over 48, we first break down the numbers into their prime factors. The square root of 27 is the square root of 3 squared times 3, which simplifies to 3√3. The square root of 48 is the square root of 16 times 3, which simplifies to 4√3. Therefore, the square root of 27 over 48 simplifies to 3√3 over 4√3, which further simplifies to 3/4.
3*square root(3) .
5 Square root 3. square root 27 = square root 9*3 = 3square root 3 3square root3 + 2square root3 = 5Square Root3 because both have a square root 3.
The square root of 3 is 1.73205081* * * * *or -1.732050812.23606798
27 27 = 3*3*3 (3 cubed = 27) 2+7 = 9 The square root of 9 is 3.
6(square root of)3